101 ways to motivate your people - Jucutan, Myra Lao (Anvil Pub., 2007)
"Motivated employees are vital to the success of the team and the organization. The company achieves greater employee performance when employees feel personal success in their jobs and relationships with others. This can be done by ensuring that employees achieve personal success, recognition and advancement."--Introduction.